MECHANISMS OF SUPPORT FOR THE YOUNG RURAL POPULATION IN THE EUROPEAN UNION - Đurić, Katarina; Njegovan, Zoran (Economics of Agriculture, 2015)
The main goal of this paper is an overview of existing and future mechanism of supporting young farmers in European Union. Positive effects of the measures of rural development policy, as well as restrictions in their operationalization were analyzed based on the insight into current reference sources and the regulations of European Union. Key recommendations for rural development policy regarding youth pertain to a higher degree of youth participation in the creation of development programs and projects, simplifcation of administrative procedures and a greater availability of information. Specifc restrictions for potential young farmers include diffcult access to farming land and a system of fnancing based on the refunds of invested resources.